Synthesis and In Vitro Biological Evaluation of Aminonaphthoquinones and Benzo[b]phenazine-6,11-dione Derivatives as Potential Antibacterial and Antifungal Compounds - Amaç Fatih Tuyun; Nilüfer Bayrak; Hatice Yıldırım; Nihal Onul; Emel Mataraci Kara; Berna Ozbek Celik (Journal of Chemistry)
A series of 2-arylamino-3-chloro-1,4-naphthoquinone derivatives (3a–h) by the reaction of 2,3-dichloro-1,4-naphthoquinone with aryl amines (2a–h) and benzo[b]phenazine-6,11-dione derivatives (4a–c) by the treatment of 2-arylamino-3-chloro-1,4-naphthoquinone derivatives (3a–h) with sodium azide were synthesized and tested for their in vitro antibacterial and antifungal activities. The results suggest that compounds 3d and 3g had potent antifungal activity against Candida albicans (MIC = 78.12 μg/mL). All synthesized compounds (3a–h, 4a–c) possessed activity against E. faecalis with MIC values of between 312.5 and 1250 μg/mL. Benzo[b]phenazine-6,11-dione derivatives (4a–c) were mostly active against Gram-positive bacteria. The structures of the new members of the series were established on the basis of their spectral properties (IR, 1H NMR, 13C NMR, and mass spectrometry).